Bimetallic Metal‐Organic Framework with High‐Adsorption Capacity toward Lithium Polysulfides for Lithium–sulfur Batteries. Issue 2 (10th June 2021) - Geng, Pengbiao; Du, Meng; Guo, Xiaotian; Pang, Huan; Tian, Ziqi; Braunstein, Pierre; Xu, Qiang
Abstract : The practical application of Li‐S batteries is largely impeded by the "shuttle effect" generated at the cathode which results in a short life cycle of the battery. To address this issue, this work discloses a bimetallic metal‐organic framework (MOF) as a sulfur host material based on Al‐MOF, commonly called (Al)MIL‐53. To obtain a high‐adsorption capacity to lithium polysulfides (Li2 S x, 4 ≤ x ≤ 8), we present an effective strategy to incorporate sulfiphilic metal ion (Cu 2+ ) with high‐binding energy to Li2 S x into the framework. Through a one‐step hydrothermal method, Cu 2+ is homogeneously dispersed in Al‐MOF, producing a bimetallic Al/Cu‐MOF as advanced cathode material. The macroscopic Li2 S4 solution permeation test indicates that the Al/Cu‐MOF has better adsorption capacity to lithium polysulfides than monometallic Al‐MOF. The sulfur‐transfusing process is executed via a melt‐diffusion method to obtain the sulfur‐containing Al/Cu‐MOF (Al/Cu‐MOF‐S). The assembled Li‐S batteries with Al/Cu‐MOF‐S yield improved cyclic performance, much better than that of monometallic Al‐MOF as sulfur host. It is shown that chemical immobilization is an effective method for polysulfide adsorption than physical confinement and the bimetallic Al/Cu‐MOF, formed by incorporation of sulfiphilic Cu 2+ into porous MOF, will provide a novel and powerful approach for efficient sulfur host materials. Abstract : A high–lithium polysulfide adsorption bimetallic MOF (Al/Cu‐MOF) is prepared through a one‐step hydrothermal method. The Al/Cu‐MOF combines the porous structure of MOF and strong chemical interaction with polysulfides of sulfiphilic Cu 2+ . When used as sulfur host materials, the assembled battery could achieve a high‐initial specific capacity and a good cyclic performance. ​